The effect of geometrical modifications to a shell and tube heat exchanger on performance and freezing risk during LNG regasification. (November 2020) - Brenk, Arkadiusz; Kielar, Jakub; Malecha, Ziemowit; Rogala, Zbigniew
Highlights: Risk of ice formation in STHX during LNG regasification was studied. Heat transfer through the boiling LNG layer was modeled as a conduction mechanism. The model of boiling LNG layer was based on available experimental data. Analysis of ice formation for various shapes of STHX tubes was conducted. Flattened tubes gave better heat transfer, higher reliability and lower pump duty. Abstract: The regasification of LNG is a crucial process in a majority of LNG applications and can be conducted in various types of heat exchangers. The low boiling temperature of LNG makes the vaporization process prone to the risk of ice formation, which can obstruct the flow of the heating fluid. This, in turn, can lead to a significant drop in pressure, decrease in heat transfer or even to the destruction of the heat exchanger itself. In a wide range of important applications, the heating fluid is often water or a water-glycol mixture, characterized by a freezing temperature that is substantially higher than the boiling temperature of LNG. Consequently, this can intensify the ice formation process. In the current research, a numerical model was proposed and developed to analyze the risk of ice formation during the LNG vaporization process within a shell-and-tube type of heat exchanger (STHX). The model consists of two distinct parts: heat transfer through the boiling LNG and the freezing dynamics of the heating fluid. To generalize the developed model for various boiling regimes a continuous and differentiable expression of the boiling curve of LNG was proposed. The expression smoothly connected the nucleate with the film boiling regions and methodically filled the gap of the transition region. The developed numerical model was used to investigate a wide range of flow conditions and various shapes and spacing of tubes within the STHX. It was shown that the risk of total freezing could be indicated by a critical value of the Reynolds number. The conducted study made it possible to define a heat-flux-to-pump-duty-ratio coefficient, which showed that flattened tubes could ensure better heat transfer, higher reliability and also decrease the pump duty needed to supply the STHX.